2014
DOI: 10.1007/s11033-014-3325-0
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling cascade in restenosis: a potential therapeutic target of public health relevance in a North American cohort of Nebraska State

Abstract: Cardiovascular disease is a leading cause of morbidity and mortality in United States, including Nebraska. Neointimal hyperplasia leading to restenosis is a major public health problem. Identification of key signaling molecules in biochemical pathways is an attractive strategy for development of predictive biomarkers in occlusive vascular diseases (OVD). Our pilot study aimed to identify the role of Wnt-frizzled signaling in restenosis in a North American cohort. North American patients (n = 9) undergoing coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Recently, Pandey and Chandravati 100 have suggested that Wnt signalling can complement public health initiatives in predicting occlusive vascular disease (restenosis after coronary artery bypass graft surgery) which is a major public health problem in the United States. Identification of new molecular mechanisms in coordination with clinical data is crucial in the development of cost-effective biomarkers for this at-risk population.…”
Section: Wnt Signalling In Cmdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Pandey and Chandravati 100 have suggested that Wnt signalling can complement public health initiatives in predicting occlusive vascular disease (restenosis after coronary artery bypass graft surgery) which is a major public health problem in the United States. Identification of new molecular mechanisms in coordination with clinical data is crucial in the development of cost-effective biomarkers for this at-risk population.…”
Section: Wnt Signalling In Cmdsmentioning
confidence: 99%
“…Identification of new molecular mechanisms in coordination with clinical data is crucial in the development of cost-effective biomarkers for this at-risk population. 100 Wnt signalling contributes to multiple levels of atherosclerosis pathogenesis: initial endothelial dysfunction, plaque instability and size of the lipid core; however, the full contribution of non-canonical and canonical Wnts in the development of atherosclerosis and CVD has yet to be elucidated in detail. Thus, therapeutics targeting Wnt signalling may provide a novel way to combat atherosclerosis.…”
Section: Wnt Signalling In Cmdsmentioning
confidence: 99%
“…It is reported that the stable neointima contains 20% VSMCs [20], suggests that VSMCs play an important role in ISR. Pandey et al found that Wnt5a mRNA was expressed in human VSMCs, as well as its receptors, such as Fzd1, Fzd2 and Fzd5 [21]. This result suggests that Wnt5a may be implicated in ISR via regulating VSMCs functions.…”
Section: Discussionmentioning
confidence: 98%